A Study of 10-Minute Delivery Apps in the e-Business Ecosystem - Jadhav, Nalini Mahesh; Gite, B S (International Journal of Engineering and Management Research, 2025)
Time never waits for anyone. In today’s fast-paced world, everyone wants everything to happen quickly. Whether it’s food delivery, grocery shopping, or medical needs, people want instant services. This demand has given rise to a new trend in business — 10-minute delivery. In this competitive era, everyone wants to stay ahead. That’s why e-business is evolving every day. Modern businesses are adopting advanced techniques and technologies to satisfy customers and provide faster services. With this background, this research paper tries to explore how these quick delivery apps have become a part of the e-business ecosystem. We will understand the significance, objectives, and impact of these apps. In this research, the focus will be on understanding how 10-minute delivery apps affect consumers, what their business model looks like, and what the future of these apps in India may hold. Major apps like Instamart, Zepto, and Blinkit have introduced this concept of 10-minute delivery and are continuously trying to improve their services. Using such apps, goods reach the customer quickly. Due to this, customers are becoming dependent on these apps. This research will also study both the advantages and disadvantages of this rapid delivery model.